2021
DOI: 10.3390/ph14111070
|View full text |Cite
|
Sign up to set email alerts
|

L-Lysine α-Oxidase: Enzyme with Anticancer Properties

Abstract: L-lysine α-oxidase (LO), one of L-amino acid oxidases, deaminates L-lysine with the yield of H2O2, ammonia, and α-keto-ε-aminocaproate. Multiple in vitro and in vivo studies have reported cytotoxic, antitumor, antimetastatic, and antitumor activity of LO. Unlike asparaginase, LO has a dual mechanism of action: depletion of L-lysine and formation of H2O2, both targeting tumor growth. Prominent results were obtained on murine and human tumor models, including human colon cancer xenografts HCT 116, LS174T, and T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 85 publications
0
19
0
2
Order By: Relevance
“…Nanomedicines are favorable to intravenous injection for the efficient delivery of drugs without any toxicity to normal cells [ 47 ]. In addition, the enzyme LO is known to cause the toxicity of L-lysine in blood plasma [ 3 ]. To verify the blood toxicity of LO, a hemolysis assay was performed and compared the activity of CS-LO-PEG HER NPs and CS-LO PEG NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanomedicines are favorable to intravenous injection for the efficient delivery of drugs without any toxicity to normal cells [ 47 ]. In addition, the enzyme LO is known to cause the toxicity of L-lysine in blood plasma [ 3 ]. To verify the blood toxicity of LO, a hemolysis assay was performed and compared the activity of CS-LO-PEG HER NPs and CS-LO PEG NPs.…”
Section: Resultsmentioning
confidence: 99%
“…L-lysine α-oxidase (LO) was first discovered in Trichoderma viride , then in T. harzianum Rifai, in the 1980s [ 1 , 2 ]. This enzyme has been shown to inhibit the proliferation of cancer cells, such as human lung squamous cell carcinoma (RERF-LC-AI), prostate cancer (PC3), cervical cancer cell line (HeLa), ovarian cancer (SKOV3), breast cancer (MCF7), colon cancers (LS174T and HT29) and erythromyeloblastoid leukemia (K562), without causing any significant damage to normal human umbilical vein endothelial cells (HUVECs) [ 3 , 4 ]. Breast and ovarian cancer cells are more sensitive to LO than others [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the experimental results of SKOV3-TR, it was confirmed that cell viability was significantly inhibited in the arginine-, glutamine-, and lysine-deprived culture conditions in SKOV3 cells (data not shown), showing the potential of targeting amino acid metabolism to suppress survival in ovarian cancer, independent of paclitaxel resistance. Previous studies revealed that arginine deprivation induced cell cytotoxicity via the autophagy pathway in ovarian cancer cells [ 41 ], and that lysine deprivation enhanced the anticancer effect through L-lysine α-oxidase-induced oxidative stress [ 54 ]. Although glutamine deprivation-induced cytotoxicity has been reported, little is known about the effects of glutamine deprivation on paclitaxel resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With a very special demand for nutrition, cancer cells increased multiple metabolic processes and overconsumed nutrients in order to meet the energy and biosynthesis required for growth [ 21 ]. In past studies, it had been found that the consumption of certain amino acids, such as asparagine, arginine, and methionine, could be applied to treat amino acid-dependent cancers [ 22 ]. In addition, the degradation of lysine could also inhibit the growth of various cancer cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%